Multiple test: the Malaysian courts' approach in determining special relationship for the doctrine of vicarious liability / Rafiqah Abd Razak … [et al.] - Abd Razak, Rafiqah; Baharuddin, Nor Adila; Ismail, Noor Farazidah; Amin Nudin, Noorsaliza; Syed Abdul Rahman, Sharifah Khalisha (Faculty of Law, 2010)
This research aims at looking at the reasons why Malaysian courts do not adopt the Multiple Test in deciding Special Relationship in the Doctrine of Vicarious Liability. The team of five members conducted this research as part of the requirement for a Degree in the Bachelor in Legal Studies (Hons.) programme in Universiti Teknologi Mara, Shah Alam in determining whether the Multiple Test is the most appropriate test to be used in determining the existence of Special Relationship in the Doctrine of Vicarious Liability. The five chapters of the research discuss the application of the Multiple Test by conducting case studies in The United Kingdom and Malaysia as to the application of the Multiple Test for Special Relationship in the Doctrine of Vicarious Liability. In most of the cases, it was found that the Multiple Test was only mentioned but was not used by the United Kingdom and Malaysian courts. The Multiple Test should be regarded as the best test as it incorporates with the Control Test and the Organisation Test to determine the existence of Special Relationship since the test will cover all types of employees.